Description of Knowledge and Attitudes of Teenagers to Sexually Transmitted Diseases in Public Senior High School 8 Banjarmasin - Nur Cahyani Ari Lestari; Syahrida Wahyu Utami; Sri Purwanti (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2021)
Sexually transmitted diseases are diseases that are transmitted through sexual intercourse with multiple partners and are a form of behavior that deviates and exceeds boundaries or is also called juvenile delinquency. Basically juvenile delinquency refers to a form of adolescent behavior that is not in accordance with the norms that exist in society. At Public Senior High School 8 in the Alalak Tengah Community Health Center, Banjarmasin City, there is one person who quit school because he wants to get married. This study aims to describe the knowledge and attitudes of adolescents against sexually transmitted diseases in Public Senior High School 8 Banjarmasin. This research was conducted at Public Senior High School 8 Banjarmasin with a descriptive research method. Population of 153 people with a sample of 62 people, the sampling technique with proposive sampling where sampling is based on a certain consideration made by the researcher. The results of the research at Public Senior High School 8 Banjarmasin were respondents who had good knowledge of 15 people (24.19%), quite 38 people (61.29%), less than 7 people (11.29%), and 2 people who were not good 23). respondents who had a supportive or positive attitude towards sexually transmitted diseases were 29 people (46.77%) and negative attitudes towards sexually transmitted diseases were 33 people (53.23%). Based on the research, it was concluded that the knowledge of Public Senior High School 8 Banjarmasin students about sexually transmitted diseases was in the moderate category and had a negative attitude.